Topical Treatment of Truncal Acne with Tretinoin Lotion 0.05% and Azelaic Acid Foam - Sharleen St. Surin-Lord; Judi Miller (Hindawi Limited, 2020)
Truncal acne is present in approximately half of all patients with facial acne but is also occasionally seen in isolation. Important considerations when selecting treatment options for adult female acne, whether on the face, back, chest, or shoulders, include patient compliance, treatment response time, tolerability of the treatment, and psychosocial impact of the disease. Oral antibiotics are widely prescribed for truncal acne due to the challenges of applying topical therapy to such an extensive body surface area. In cases of severe inflammatory and nodular acne vulgaris, this may be a reasonable consideration; however, oral antibiotics should only be used for short durations. Overprescription contributes to microbial resistance and may cause disruption of the gastrointestinal microbiome. In many cases of mild, moderate, or even severe truncal acne, combinations of topical therapies may be valid alternatives. The introduction of foam formulations with enhanced percutaneous absorption and tretinoin lotion formulations that incorporate moisturizing/hydrating agents challenges the previously held idea that effective and tolerable treatment of truncal acne requires oral treatment. This case series describes four female African-American patients with truncal acne successfully treated with a combination of tretinoin lotion 0.05% and azelaic acid 15% foam.